ABS-maleated SEBS blend as a 3D printable material. Issue 2 (2nd April 2016) - Siqueiros, J. Gilberto; Schnittker, Kevin; Roberson, David A.
ABSTRACT: A key enabler for the advancement of material extrusion 3D printing is the implementation of new printable materials with a wide variety of physical properties. The focus of this study is the development of 3D printable polymer blends based on compounding acrylonitrile butadiene styrene (ABS) with styrene ethylene butylene styrene. Here the mechanical properties of the resulting novel material systems were manipulated through the change of mixture composition. The novel blends were evaluated based on mechanical testing and fracture surface analysis. Additionally, the rheological characteristics were determined based on melt flow index values. Key results were the significant increase in elongation at break values from 8.53% (ABS baseline) to 1506.57% (rubberised ABS) and the drastic difference in fracture surface morphology when comparing the various blends to ABS.